2005
DOI: 10.1007/s10237-004-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

A cartilage growth mixture model for infinitesimal strains: solutions of boundary-value problems related to in vitro growth experiments

Abstract: PUBLISHED CITATIONKlisch SM, Sah RL, Hoger A. A cartilage growth mixture model for infinitesimal strains:solutions of boundary-value problems related to in vitro growth experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…This assumption is supported by our solution to the dynamic growth problem presented in Klisch et al (2005b). We first proposed the incremental growth boundary-value problem in Klisch et al (2001) and later modified it in Klisch (2006b) to be compatible with the finite element method.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…This assumption is supported by our solution to the dynamic growth problem presented in Klisch et al (2005b). We first proposed the incremental growth boundary-value problem in Klisch et al (2001) and later modified it in Klisch (2006b) to be compatible with the finite element method.…”
Section: Introductionmentioning
confidence: 82%
“…Future work will extend the bimodular stressstrain equation for the collagen constituent to include anisotropic behavior (Klisch 2006a). Also, it has been suggested that to accurately model specific growth experiments a collagen remodeling parameter (related to collagen-specific crosslink or fibril binding molecules) should be included that changes the mechanical properties of the collagen constituent (Klisch et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations